2022
DOI: 10.3390/ijms24010013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bromodomain and Extraterminal (BET) Proteins in Controlling the Phagocytic Activity of Microglia In Vitro: Relevance to Alzheimer’s Disease

Abstract: The correct phagocytic activity of microglia is a prerequisite for maintaining homeostasis in the brain. In the analysis of mechanisms regulating microglial phagocytosis, we focused on the bromodomain and extraterminal domain (BET) proteins: Brd2, Brd3, and Brd4, the acetylation code readers that control gene expression in cooperation with transcription factors. We used pharmacological (JQ1) and genetic (siRNA) inhibition of BET proteins in murine microglial cell line BV2. Inhibition of BET proteins reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…In mice, JQ1 is well tolerated even after chronic treatment, and it efficiently enters the brain (AUC brain /AUC plasma = 98%) [43,45,48]. Our previous data indicated that in mouse microglia in vitro JQ1 reduced the expression of the Cd33 gene by 83% [44]. In the current study, it was observed that JQ1 reduced the level of Cd33 mRNA in the mouse hippocampus during SIR, but had no effect in the corresponding control.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In mice, JQ1 is well tolerated even after chronic treatment, and it efficiently enters the brain (AUC brain /AUC plasma = 98%) [43,45,48]. Our previous data indicated that in mouse microglia in vitro JQ1 reduced the expression of the Cd33 gene by 83% [44]. In the current study, it was observed that JQ1 reduced the level of Cd33 mRNA in the mouse hippocampus during SIR, but had no effect in the corresponding control.…”
Section: Discussionsupporting
confidence: 47%
“…In the current study, it was observed that JQ1 reduced the level of Cd33 mRNA in the mouse hippocampus during SIR, but had no effect in the corresponding control. We can assume the cerebral action of JQ1, therefore, its inhibitory effect on microglial phagocytosis [44] cannot be completely excluded. Based on these data, we propose that inhibitors of BET proteins may prevent inflammation-evoked changes in the expression of the Cd33 gene and, therefore, may be used to attenuate CD33-dependent signalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning neurodegenerative conditions, only few data are available about the prospective impact of BET inhibition in HD and PD, whereas most research has focused on AD. Even though few in vitro studies pointed out a detrimental role of BET inhibition in AD pathology [ 146 ], a growing body of evidence underlines that BET blockade could counteract cognitive dysfunction and neuroinflammation in different cellular and animal models [ 23 , 143 , 145 ]. The discrepancy among these studies may be explained considering the specific experimental models, as well as drug dosage and treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…However, different from other published evidence, they failed in detecting cognitive improvement; this discrepancy can be explained by divergences in the experimental setup, such as age of the animals, dosage used for treatments, animal model training, and behavioral assessment [ 17 ]. The relevance of BET proteins to neuroinflammation in AD was sustained by another study showing that BET blockade reduced phagocytic activity of the microglial cell line BV2; the effect was dependent on the downregulation of phagocytosis-related genes which were involved in the pathogenetic mechanisms of AD [ 145 ]. The pharmacological potential of BET inhibition in AD has also been investigated in co-treatment with HDAC inhibitors.…”
Section: Involvement Of Bet Proteins In Neuropathological Conditionsmentioning
confidence: 99%